(untitled) (Genius Repository, 2023)
This scientific article outlines the socio-political views and relations of the Samarkand Jadids. They have expressed their views on various incidents in society. In particular, it was highlighted that the development of the national language and the excessive erosion of the Russian language, as well as the freedom, independence of the people and the self-determination of each nation, raised the issue of rights. In the absence of funding for the national education system, the moral crisis and its socio-political causes have been disclosed.